Nucleobase modification as redox DNA labelling for electrochemical detection - Hocek, Michal; Fojta, Miroslav (Chemical Society reviews, 2011)
Basic aspects of DNA electrochemistry with a strong focus on the use of modified nucleobases as redox probes for electrochemical bioanalysis are reviewed. Intrinsic electrochemical properties of nucleobases in combination with artificial redox-active nucleobase modifications are frequently applied in this field. Synthetic approaches (both chemical and enzymatic) to base-modified nucleic acids are briefly summarized and their applications in redox labelling are discussed. Finally, analytical applications including DNA hybridization, primer extension, PCR, SNP typing, DNA damage and DNA-protein interaction analysis are presented (critical review, 91 references).
Keywords: Electrochemistry; barvení a značení; oligodeoxyribonukleotidy; oxidace-redukce; Humans; Staining and Labeling; Oxidation-Reduction; elektrochemie; DNA; lidé; Oligodeoxyribonucleotides